Dragging developers towards the core: How the free/libre/open source software community enhances developers' contribution - Francesco Rullani (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2006)
The paper presents a dynamic perspective on the landscape of Free/Libre/Open Source Software (FLOSS) developers' motivations and tries to isolate mechanisms sustaining developers' contribution over time. The first part of the paper uses data gathered by the empirical studies relative to the FLOSS case to judge the relative importance of each group of incentives detected by the literature. In the second part of the paper, the same data are used to further characterize developers' motivations in dynamics terms. In particular, the study shows that the relative importance of different incentives do change over time. Drawing inspiration from the literature aimed at explaining these changes, the third part of the paper identifies a specific mechanism fostering developers' contribution to the community activities, namely that: Independently of developers' exogenous preferences, the more their exposure to the FLOSS community social environment, the more their contribution to the community activities. The key point of this hypothesis is that, if the exposure to the FLOSS community social environment is able to foster developers' contribution beyond the level granted by their predetermined preferences, this leads directly to the evidence that the FLOSS community is provided with a mechanism sustaining and enhancing developers' incentives to produce and diffuse code. In the last part of the paper, data relative to 14,497 developers working on SourceForge.net during two years (2001-2002) are employed to estimate a model testing the aforementioned hypothesis. Endogeneity problems are explicitly accounted for, and robustness checks are performed in order to make sure that the observed confirmation of the hypothesis is actually an empirically grounded result.
Keywords: O31; L86; 330; Free/Libre/Open Source Software; Incentives to Innovate; Dynamics of Motivations; Cooperation; Community; Motivation; Ökonomischer Anreiz; Softwareentwicklung; Open Source